Exploring the Effectiveness of Mediation in Resolving Disputes in the Indonesian Administrative Court - Amarini, Indriati; Ismail, Noorfajri; Saefudin, Yusuf; Attamimi, Zeehan Fuad; Hidayah, Astika Nurul (Universitas Negeri Semarang, 2024)
This study analyzes mediation in administrative dispute resolution in Indonesian Administrative Courts. The settlement of administrative disputes through mediation is not recognized in the Administrative Court procedural law. Mediation in the dispute resolution process in Administrative Courts is still a matter of debate. One of the parties to the dispute is a public body or official who is included in the realm of public law, so that mediation is not possible. The execution of Administrative Court decisions that have permanent legal force does not guarantee justice and legal certainty. This research aims to analyze the development and implementation of mediation in settlement of public disputes in Administrative Courts. The research method used is doctrinal research or library research with secondary data sources in the form of legislation on Administrative Courts, Supreme Court regulations on mediation, and scientific journals of research results. The results showed that mediation in public dispute resolution is used as an alternative to dispute resolution and has long been applied in several countries. Mediation in administrative dispute resolution can be carried out in two ways. First, mediation can be carried out outside the Administrative Court, and then the lawsuit is revoked. Second, mediation can be carried out through Court-connected mediation in the Administrative Court. There is a need to develop and strengthen the application of Court-connected mediation for administrative dispute resolution from the aspects of procedural law and Administrative Court resources that support the mediation process.